Aggregated knowledge from a small number of debates outperforms the wisdom of large crowds. (February 2018) - Navajas, Joaquin; Niella, Tamara; Garbulsky, Gerry; Bahrami, Bahador; Sigman, Mariano
Abstract The aggregation of many independent estimates can outperform the most accurate individual judgement1–3 . This centenarian finding1, 2, popularly known as the 'wisdom of crowds'3, has been applied to problems ranging from the diagnosis of cancer4 to financial forecasting5 . It is widely believed that social influence undermines collective wisdom by reducing the diversity of opinions within the crowd. Here, we show that if a large crowd is structured in small independent groups, deliberation and social influence within groups improve the crowd's collective accuracy. We asked a live crowd (N = 5, 180) to respond to general-knowledge questions (for example, "What is the height of the Eiffel Tower?"). Participants first answered individually, then deliberated and made consensus decisions in groups of five, and finally provided revised individual estimates. We found that averaging consensus decisions was substantially more accurate than aggregating the initial independent opinions. Remarkably, combining as few as four consensus choices outperformed the wisdom of thousands of individuals. The collective wisdom of crowds often provides better answers to problems than individual judgements. Here, a large experiment that split a crowd into many small deliberative groups produced better estimates than the average of all answers in the crowd.